Classical and quantum dynamics of the sphere; International Journal of Geometric Methods in Modern Physics; Vol. 13 - Lasukov V. V. Vladimir Vasilievich; Moldovanova E. A. Evgeniya Aleksandrovna; Abdrashitova M. O. Mariya Ovseevna; Malik Hitendra Kumar H. K. Hitendra Kumar; Gorbacheva E. S. Ekaterina Sergeevna (2016, 2016)
Title screen